Dynamics of structural, functional and vegetative changes of heart under the influence of combined therapy with the use of ursodeoxycholic acid and L-arginine in patients with coronary heart disease associated with nonalcoholic fatty liver disease - N. S. Mykhailovska; L. Ye. Miniailenko (Patologìâ)
Objective: to study the effect of the ursodeoxycholic acid and L-arginine combination on the background of basic therapy on the structural and functional state of the heart and indicators of the autonomic nervous system in patients with coronary heart disease combined with the non-alcoholic fatty liver disease.